2018
DOI: 10.1002/psc.3120
|View full text |Cite
|
Sign up to set email alerts
|

Ascidiacyclamides containing oxazoline and thiazole motifs assume square conformations and show high cytotoxicity

Abstract: Four cyclic octapeptides were designed from ascidiacyclamide [cyclo(-Ile-Oxz-D-Val- Thz-) ] (ASC, 1) to investigate the effects of oxazoline (Oxz) and thiazole (Thz) rings on the structures and cytotoxicities of the peptides. cyclo(-Ile-Thz-D-Val-Oxz-) (2) had the same number of Oxz and Thz rings as ASC, but the ring positions were switched. cyclo(-Ile-Oxz-D-Val-Thz-Ile-Thz-D-Val-Thz-) (3) and cyclo(-Ile-Thz-D-Val-Oxz-Ile-Thz-D-Val-Thz-) (4) contained one Oxz and three Thz rings within the molecule. All Oxz ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…We have well established that measuring the CD spectral changes in this solvent system is a useful means of monitoring the conformational equilibrium between the square and folded forms of ascidiacyclamides. [7][8][9]20 Previously recorded CD spectra for 1 are also shown in The spectral changes observed with 11 showed the same features as 1 in this solvent system. The conformation of 11 in CH 3 CN solution was the square form, which was converted to the folded form through TFE titration.…”
Section: Spectrasupporting
confidence: 58%
See 1 more Smart Citation
“…We have well established that measuring the CD spectral changes in this solvent system is a useful means of monitoring the conformational equilibrium between the square and folded forms of ascidiacyclamides. [7][8][9]20 Previously recorded CD spectra for 1 are also shown in The spectral changes observed with 11 showed the same features as 1 in this solvent system. The conformation of 11 in CH 3 CN solution was the square form, which was converted to the folded form through TFE titration.…”
Section: Spectrasupporting
confidence: 58%
“…S43 †), and most T3ASC molecules reportedly retain the square form even in solution. 20 On the other hand, dASC, cyclo(-Ile-alloThr-D-Val-Thz-) 2 , which lacks the Oxz rings of 1, assumes a folded form in both solid and solution states (Fig. S44 †).…”
Section: Introductionmentioning
confidence: 99%
“…Cyclic thiazole-and oxazoline-containing octapeptides and patellamides, isolated from marine tunicates, have also been an object of modification. It has been shown that changes in the position of thiazoles and oxazolines in ascidiacyclamide can influence their cytotoxic activity, obtaining inactive derivatives and 10 times more active compounds depending on the conformations attained [91].…”
Section: Cyclic Peptidesmentioning
confidence: 99%
“…This coordination leads the Thz-Thr-Oxz unit to be relatively flat and to form four flanking five-membered rings. The chiral modifications or exchange of the azole rings makes the ASC molecule relatively flat (Asano et al, 2001b(Asano et al, , 2002b(Asano et al, , 2018, but the planarity is low in comparison to the metal-coordinated structure. The least-squares planes of the Thz-Ile-Oxz units, calculated using the Cu1, N1, N7 and N37 atoms or the Cu2, N17, N21 and N27 atoms, face one another at an angle of 19.5 ( Fig.…”
Section: Figurementioning
confidence: 99%
“…This restriction arises because the flexibility of their precursor amino acids is lost from Oxz and Thz. The bond rotation is limited to back and forth movement at the planar azole rings (Ishida et al, 1992;Hambley et al, 1992;Asano et al, 2001aAsano et al, , 2018. Consequently, ASC exists in a conformational equilibrium between two major conformers (folded and square) (Doi et al, 1999;Asano et al, 2002aAsano et al, , 2003Asano et al, , 2011Asano et al, , 2014Asano et al, , 2016.…”
Section: Introductionmentioning
confidence: 99%